β1 Integrins as Therapeutic Targets to Disrupt Hallmarks of Cancer - Blandin, Anne-Florence; Renner, Guillaume; Lehmann, Maxime; Lelong-Rebel, Isabelle; Martin, Sophie; Dontenwill, Monique (Frontiers in Pharmacology, 2015)
Integrins belong to a large family of αβ heterodimeric transmembrane proteins first recognized as adhesion molecules that bind to dedicated elements of the extracellular matrix and also to other surrounding cells. As important sensors of the cell microenvironment, they regulate numerous signaling pathways in response to structural variations of the extracellular matrix. Biochemical and biomechanical cues provided by this matrix and transmitted to cells via integrins are critically modified in tumoral settings. Integrins repertoire are subjected to expression level modifications, in tumor cells and in surrounding cancer-associated cells, implicated in tumor initiation and progression as well. As critical players in numerous cancer hallmarks, defined by Hanahan and Weinberg in 2011, integrins represent pertinent therapeutic targets. We will briefly summarize here our current knowledge about integrin implications in those different hallmarks focusing primarily on β1 integrins.